The impact of submersed aquatic vegetation on the development of river mouth bars. Issue 7 (14th February 2019) - Lera, Sara; Nardin, William; Sanford, Lawrence; Palinkas, Cindy; Guercio, Roberto
Abstract: This work is inspired by the sudden resurgence of the submersed aquatic vegetation (SAV) bed in the Chesapeake Bay (USA). Because the SAV bed occurs at the mouth of the Bay's main tributary (Susquehanna River), it plays a significant role in modulating sediment and nutrient inputs from the Susquehanna to the Bay. Previous model studies on the impact of submersed aquatic vegetation on the development of river mouth bars lacked a complete mechanistic understanding. This study takes advantage of new advances in 3D computational models that include explicit physical‐sedimentological feedbacks to obtain this understanding. Specifically, we used Delft3D, a state‐of‐the‐art hydrodynamic model that provides fine‐scale computations of three‐dimensional flow velocity and bed shear stress, which can be linked to sediment deposition and erosion. Vegetation is modeled using a parameterization of hydraulic roughness that depends on vegetation height, stem density, diameter, and drag coefficient. We evaluate the hydrodynamics, bed shear stresses, and sediment dynamics for different vegetation scenarios under conditions of low and high river discharge. Model runs vary the vegetation height, density, river discharge, and suspended‐sediment concentration. Numerical results from the idealized model show that dense SAV on river mouth bars substantially diverts river discharge into adjacent channels and promotes sediment deposition at ridge margins, as well as upstream bar migration. Increasing vegetation height and density forms sandier bars closer to the river mouth and alteration of the bar shape. Thus, this study highlights the important role of SAV in shaping estuarine geomorphology, which is especially relevant for coastal management. © 2019 John Wiley & Sons, Ltd. Abstract : The presence of submersed aquatic vegetation (SAV) modifies hydrodynamics and sediment transport processes, and therefore also the morphological evolution of river mouth bars. SAV on the bar top decreased the longitudinal velocity over the top of the developing bar and increased the transverse velocity over the bar, resulting in a velocity redistribution around the bar. Increasing the vegetation height and density decreased the bed shear stress over the bar, resulting in a reduction of sediment transport.